EFL teachers’ attitudes towards online learning in Palestinian high schools during the COVID-19 pandemic - Mohammed Farrah; Israa Othman Zalloum (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
The purpose of this study is to identify teachers’ perceptions towards online learning in teaching English language during the COVID-19 pandemic in Palestinian schools. The study sample included 418 male and female EFL teachers working in the schools of the education directorates of the Palestinian Ministry of Education in the West Bank and Gaza Strip. The researcher employed a mixed method of qualitative and quantitative methods. Teachers were asked to fill a 5-point Likert scale questionnaire, including 59 items and answer three open-ended questions. The researchers used the statistical analysis method. To analyze the three open-ended questions, the researchers employed the content analysis. Study findings have shown that EFL teachers had positive attitudes towards online learning in an emergency. Results also demonstrate that online learning developed students’ communicative competence. Moreover, the study has portrayed that both high and primary school EFL teachers had positive attitudes towards online learning as it offered many opportunities for teachers and their students. Findings also reveal that teachers and their students faced many challenges of online EFL learning. The study recommends improving the technological infrastructure and online educational applications. It also suggests holding sufficient training courses and workshops for teachers, parents, and students.